Molecular cloning and characterization of taurocyamine kinase from Clonorchis sinensis: a candidate chemotherapeutic target. - Jing-Ying Xiao; Ji-Yun Lee; Shinji Tokuhiro; Mitsuru Nagataki; Blanca R Jarilla; Haruka Nomura; Tae Im Kim; Sung-Jong Hong; Takeshi Agatsuma (Public Library of Science (PLoS), 2013)
BACKGROUND: Adult Clonorchis sinensis lives in the bile duct and causes endemic clonorchiasis in East Asian countries. Phosphagen kinases (PK) constitute a highly conserved family of enzymes, which play a role in ATP buffering in cells, and are potential targets for chemotherapeutic agents, since variants of PK are found only in invertebrate animals, including helminthic parasites. This work is conducted to characterize a PK from C. sinensis and to address further investigation for future drug development. METHODOLOGY/PRINCIPAL FINDINGS: [corrected] A cDNA clone encoding a putative polypeptide of 717 amino acids was retrieved from a C. sinensis transcriptome. This polypeptide was homologous to taurocyamine kinase (TK) of the invertebrate animals and consisted of two contiguous domains. C. sinensis TK (CsTK) gene was reported and found consist of 13 exons intercalated with 12 introns. This suggested an evolutionary pathway originating from an arginine kinase gene group, and distinguished annelid TK from the general CK phylogenetic group. CsTK was found not to have a homologous counterpart in sequences analysis of its mammalian hosts from public databases. Individual domains of CsTK, as well as the whole two-domain enzyme, showed enzymatic activity and specificity toward taurocyamine substrate. Of the CsTK residues, R58, I60 and Y84 of domain 1, and H60, I63 and Y87 of domain 2 were found to participate in binding taurocyamine. CsTK expression was distributed in locomotive and reproductive organs of adult C. sinensis. Developmentally, CsTK was stably expressed in both the adult and metacercariae stages. Recombinant CsTK protein was found to have low sensitivity and specificity toward C. sinensis and platyhelminth-infected human sera on ELISA. CONCLUSION: CsTK is a promising anti-C. sinensis drug target since the enzyme is found only in the C. sinensis and has a substrate specificity for taurocyamine, which is different from its mammalian counterpart, creatine.